DETERMINANT FACTORS ON HEALTH INSURANCE PURCHASE BEHAVIOUR OF MILLENNIALS IN MALAYSIA: A CONCEPTUAL PAPER - Liew, Ming Hwa; Shu, Swee Fang; Chong, Kim Mee; Mohammad, Farajnezhad (INTI International University, 2023)
In the current living environment, health insurance has become an essential necessity, especially with the relentless pace of medical inflation. Unfortunately, a significant portion of the population remains without adequate coverage. This study focuses on Millennials in Malaysia, a population of around 11 million with the financial capability to afford health insurance. Apparently, millennials are born between 1981 and 1996 (ages 23 to 38 in 2019). Despite this, the actual insured population in Malaysia is only at 41%, signifying a lack of insurance protection. The key factors influencing health insurance purchase behavior among Millennials are examined in this research, including financial literacy, insurance premium affordability, and insurer brand equity. The research objectives in this study serve as the guiding pillars that shape the purpose of the investigation. The core focus of this research revolves around understanding the health insurance purchase behavior of Malaysia's Millennials. The objectives are designed to delve into the relationship between various key factors and this behavior. This research offers novel insights into the health insurance purchase behavior of Millennials in Malaysia. It highlights the financial literacy of individuals as a key driver in insurance decisions, emphasizing the need for financial education and literacy programs. Furthermore, the study underlines the importance of making insurance premiums more affordable to encourage participation. Finally, it reinforces the value of insurer brand equity in attracting Millennials to health insurance, prompting insurance providers to focus on building and maintaining their brand reputation.